State support policy for renewable energy development in emerging economies: the case of Ukraine. (30th April 2021) - Kurbatova, Tetiana; Sotnyk, Iryna; Kubatko, Oleksandr; Baranchenko, Yevhen; Arakpogun, Emmanuel Ogiemwonyi; Roubik, Hynek
This paper investigates the role of state policies in supporting renewable energy development in emerging economies by drawing an example from Ukraine. The economic mechanisms aimed at promoting electricity generation from renewable sources, namely, the feed-in tariff, credit programs in renewable energy field, tax and customs privileges as well as indirect mechanisms, are considered in the context of business and household sectors. Particular attention is paid to the assessment of the impact of the motivational mechanisms on the deployment of renewable energy generation capacities introduced in Ukraine from 2009-2018. Despite the state support of renewable energy development and the positive tendencies toward the operational renewable energy facilities, the green electricity share in Ukraine's final electricity consumption remains insignificant. In view of this, this paper explores the barriers impeding the large-scale deployment of renewable energy and makes recommendations for improvement, including the need for changes in the state support mechanisms.